2017
DOI: 10.1007/s00248-017-1060-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependence of Predator-Prey Dynamics in Interactions Between the Predatory Fungus Lecophagus sp. and Its Prey L. inermis Rotifers

Abstract: Temperature is considered an important factor that influences the bottom-up and top-down control in water habitats. We examined the influence of temperature on specific predatory-prey dynamics in the following two-level trophic system: the predatory fungus Lecophagus sp. and its prey Lecane inermis rotifers, both of which originated from activated sludge obtained from a wastewater treatment plant (WWTP). The experiments investigating the ability of conidia to trap rotifers and the growth of fungal mycelium wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[28] and Lecophagus sp. clones [39]. Rotifers are trapped by adhesive knobs of fungus usually by mouth region, then Fig.…”
Section: Discussionmentioning
confidence: 98%
“…[28] and Lecophagus sp. clones [39]. Rotifers are trapped by adhesive knobs of fungus usually by mouth region, then Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Rotifers inhabiting activated sludge are also endangered by predacious fungi (Pajdak-Stós et al 2016 ; Fiałkowska and Pajdak-Stós 2018 ). Our experiments showed that rotifers subjected simultaneously to PAX solution and conidia of Lecophagus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Lecophagus sp. strain Z1 originates from a wastewater treatment plant located in southern Poland, as detailed by Fiałkowska and Pajdak-Stós ( 2018 ). The strain was isolated to pure culture on potato dextrose agar using the methods of Barron ( 2004 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Ciliates and heliozoans engulf whole rotifers (Wallace et al, 2015). (2) Soil and aquatic fungi feed as saprophytic parasites on rotifers and nematodes (Barron, 1980;Robb & Barron, 1982;Barron & Szijarto, 1984;Fialkowska & Pajdak-Stós, 2018).…”
Section: Prefacementioning
confidence: 99%